DESIGN AND MARKET TESTING OF THE MERDEKA BELAJAR-KAMPUS MERDEKA WEBSITE: EVIDENCE FROM INDONESIA - David Sukardi Kodrat; Melinda Alfiani Rosida Dewi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The aim of this study was to examine stakeholder connections horizontally including: Government, Universities, Partners, Lecturers, Admins, and students on the UC’S MBKM website regarding the ease and way users interact with the system. This study uses the market testing method with usability testing. The total sample is 20 respondents which are students, lecturer, and industry. This research using purposive sampling. The procedure for usability testing follows the following steps, namely: (1) collecting respondents, (2) using a comfortable room, and (3) recording the entire testing process. In usability testing, respondents are asked to complete a series of tasks while being observed. In a web-based information system, testing focuses on the convenience felt by users in finding what they are looking for, how users interact with the information provided (direct anipulation, menu selection, form fill in, command language, and natural language), how users search information, and how they act after obtaining the required information. UC’s MBKM website design uses a dynamic website that allows the content to always change. This website makes it easy to manage data needed at the university level. This data is useful for providing information related to specialization in the types of student activities at Universitas Ciputra which can be used as a monitoring and evaluation tool to determine goals and strategies for achieving each form of MBKM, determine curriculum direction, and add partners who work with the Study Program.